EVALUATING THE TIME AND COST EFFICIENCY OF PUBLIC TRANSPORT SYSTEM IN DELHI - Singh, Kamini; Singh, Anant Pratap (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The National Capital Region of Delhi is ranked third as the largest built-up urban area in the world with a population density of about 14000 people per square kilometer. A complex system of public transit, paratransit and non-motorized transit system with last-mile connectivity is integral for such large areas to perform efficiently and promote sustainable transportation systems.To understand these urban processes and related space-syntax, it is crucial to understand which mode of public transport is preferred by the user and why. The user choices for a particular mode of transportation are primarily dependent on the time-cost relation of the mode. The present paper evaluates the efficiency of four modes of public and para-transit transport systems in the city of Delhi. The key modes identified are a combination of metro, bus, auto and taxi systems. The data on travel time and travel costs is collected and compared for the three selected routes. This shall be done by comparing four modes on three routes to generate 12 permutations. The selected routes have varying origin and same destination with route length of 20 kms, 12 kms and 7.1 kms respectively. The efficiency of the transportation system is evaluated on 9 parameters - velocity, Cost of vehicle & infrastructure, Travel Cost, Travel Time, Capacity, Flexibility, Aesthetics, Comfort and Maintenance. The research identifies the travel distance and settlement density to be critical elements in the user decision-making process and hence are key parameters to be considered in planning for public transportation in complex metropolitan cities.